2013
DOI: 10.3389/fnagi.2013.00041
|View full text |Cite
|
Sign up to set email alerts
|

History of mild traumatic brain injury is associated with deficits in relational memory, reduced hippocampal volume, and less neural activity later in life

Abstract: Evidence suggests that a history of head trauma is associated with memory deficits later in life. The majority of previous research has focused on moderate-to-severe traumatic brain injury (TBI), but recent evidence suggests that even a mild TBI (mTBI) can interact with the aging process and produce reductions in memory performance. This study examined the association of mTBI with memory and the brain by comparing young and middle-aged adults who have had mTBI in their recent (several years ago) and remote (se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
3
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(106 citation statements)
references
References 63 publications
(81 reference statements)
8
92
3
3
Order By: Relevance
“…The effects of TBI on the normal synchrony of neuronal networks and how it leads to cognitive impairments are likely to be complex,38, 39 and the exact nature and timing of this network dysfunction in our model remains to be elucidated. Nevertheless, our observations are consistent with the findings from clinical studies suggesting that r‐mTBI associated with white matter changes has long‐term implications for brain communication40 and cognitive functioning 41, 42, 43, 44…”
Section: Discussionsupporting
confidence: 92%
“…The effects of TBI on the normal synchrony of neuronal networks and how it leads to cognitive impairments are likely to be complex,38, 39 and the exact nature and timing of this network dysfunction in our model remains to be elucidated. Nevertheless, our observations are consistent with the findings from clinical studies suggesting that r‐mTBI associated with white matter changes has long‐term implications for brain communication40 and cognitive functioning 41, 42, 43, 44…”
Section: Discussionsupporting
confidence: 92%
“…The outcome of the study is compatible with findings from other studies. However, in contrast to previous studies [1,13,16,17,19,[20][21][22][23], the MTBI patients showed no significantly reduced speed of information processing as was evaluated with the PASAT. An overview of the results of this study can be seen in Table 1.…”
Section: Cognitive Problems After Mild Traumatic Brain Injurycontrasting
confidence: 51%
“…In MTBI patients, mild impairments in speed of information processing, (sustained, divided, focused and/or alternating) attention and (auditory-verbal and/or visuospatial) memory have been found [1,13,16,17,19,[20][21][22][23]. With regard to memory, most patients displayed deficits concerning the storage of new information into memory and/ or the reproduction of recently learned information from memory.…”
Section: Cognitive Problems After Mild Traumatic Brain Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have revealed deficits in multiple neurocognitive domains following TBI, such as attention, visuospatial ability, memory and executive function (Carlsson et al 1987;Konrad et al 2011;Ponsford et al 2008;De Beaumont et al 2009;Himanen et al 2006;Isoniemi et al 2006;Monti et al 2013). Others have demonstrated the utility of post-injury neuropsychological testing in predicting which patients develop chronic neurocognitive impairments (Carlsson et al 1987;Konrad et al 2011;Ponsford et al 2008;De Beaumont et al 2009;Himanen et al 2006;Monti et al 2013). One such study (n = 105) showed that cognitive flexibility and reaction times testing in the emergency department predicted symptoms one month following TBI in the pediatric population (Brooks et al 2016).…”
Section: Sleep and Neurocognitionmentioning
confidence: 99%